PROFILE OF VITAMIN D DEFICIENCY IN MANGALORE - NANDINI. M; ASHOK PRABHU K; ASHOK PRABHU K; ASHA KAMATH K; AISHWAINEE V G (International Journal of Pharma and Bio Sciences, 2014)
Recent studies, reporting the prevalence of vitamin D deficiency (VDD) worldwide prompted us to assess the vitamin D status in various age groups and gender. Data of 771 subjects, who got their vitamin D levels checked at KMC Hospital, Ambedkar circle, Mangalore, were analyzed. 60% of the subjects were vitamin D deficient while only 20% had sufficient levels. The percentage of subjects with vitamin D deficiency (VDD) was highest in the age group of 21-30. The relative insufficiency was more prevalent in the age group of 1-10. The subjects with sufficient vitamin D levels belonged to the age group of 1-10 and surprisingly so even in the age group of >70 years. Males and females seem to be equally affected by this deficiency. The present study shows that vitamin D deficiency is prevalent in all age groups which needs public health intervention. However the normal range of vitamin D obtained is 17.65 - 19.56 which questions the prevalence of VDD in Mangalore.